Application of ectomycorrhizal fungi in rooting of Scots pine fascicular shoots - Niemi, Karoliina; Salonen, Maija; Ernstsen, Arild; Heinonen-Tanski, Helvi; Häggman, Hely (Canadian Journal of Forest Research, 2000)
The ectomycorrhizal fungi, Pisolithus tinctorius (Pers.) Coker & Couch and three Paxillus involutus (Batsch) Fr. strains, were used to enhance in vivo rooting in fascicular shoots of 49 Scots pine (Pinus sylvestris L.) genotypes representing seed families from southern and northern Finland. Inoculation with specific fungi either increased the rooting percentage or accelerated root formation expressed as an increased number of adventitious roots per cutting. Only one of the six seed families gave no positive response. The relationship between the in vitro production of free and conjugated forms of indole-3-acetic acid (IAA) by the fungi and rooting was also investigated. Pisolithus tinctorius was the only significant producer of IAA in the absence of exogenous tryptophan. All the Paxillus involutus strains also synthesized both free and conjugated IAA but did that actively only from exogenous tryptophan. In vitro production of IAA did not correlate with root induction in vivo, but the rooting responses depended on the fungus strains and the Scots pine seed families and (or) genotypes within families. This indicates that in vitro IAA production capacity cannot be the only criterion when selecting ectomycorrhizal fungi for rooting in vivo and that specific genotype-genotype interactions play a key role in root initiation.